2020
DOI: 10.1177/1591019920961604
|View full text |Cite
|
Sign up to set email alerts
|

Virtual 2D angiography from four-dimensional digital subtraction angiography (4D-DSA): A feasibility study

Abstract: Background Digital subtraction angiography (DSA) remains the gold standard for angiographic evaluation of cerebrovascular pathology, however, multiple acquisitions requiring additional time and radiation are often needed. In contrast, 3D-DSA provides volumetric information from a single injection but neglects temporal information. Four-dimensional-DSA (4D-DSA) combines temporal information of 2D-DSA with volumetric information of 3D-DSA to provide time-resolved tomographic 3D reconstructions, potentially reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Previous study also attempted to use the virtual 2D angiography generated from 4D DSA as a substitution for conventional 2D DSA to reduce overall time, contrast, and radiation dose from multiple 2D acquisitions. 14 Their results showed that the spatial resolution of the virtual 2D DSA was not comparable to conventional 2D DSA, especially in small vessels. Combined with our results, we can conclude that 4D DSA cannot be used as a substitution for 2D…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous study also attempted to use the virtual 2D angiography generated from 4D DSA as a substitution for conventional 2D DSA to reduce overall time, contrast, and radiation dose from multiple 2D acquisitions. 14 Their results showed that the spatial resolution of the virtual 2D DSA was not comparable to conventional 2D DSA, especially in small vessels. Combined with our results, we can conclude that 4D DSA cannot be used as a substitution for 2D…”
Section: Discussionmentioning
confidence: 97%
“…Furter increasing the spatial resolution in future prototype versions might allow to better resolve vessels, which are located very close to each other. Previous study also attempted to use the virtual 2D angiography generated from 4D DSA as a substitution for conventional 2D DSA to reduce overall time, contrast, and radiation dose from multiple 2D acquisitions 14 . Their results showed that the spatial resolution of the virtual 2D DSA was not comparable to conventional 2D DSA, especially in small vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The most technically challenging step in TIPS procedure, and frequently the longest, is the puncture of the PV following HV access [16,17]. Double C-arm DSA has been widely used in clinical practice, especially in neurointerventional practice [18].…”
Section: Discussionmentioning
confidence: 99%
“…Computer-assisted radio monitoring (CARM) and cone-beam computed tomography systems are the methodologies used for developing and measuring volume in the vascular body and are the primary techniques encompassed in four-dimensional (4D) DSA (or time-resolved DSA) [ 8 , 9 ]. The only limitation of digital subtraction angiogram is the contrast-induced procedure and its risk of possessing ionizing radiation; however, the advantages outweigh the risk by a huge margin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%